Percutaneous micro-axial flow pump use during non-emergent high-risk PCI: Systematic review and meta-analysis - Elbenawi, Hossam; Doma, Mohamed; Cangut, Busra; Abdelgalil, Mahmoud Shaaban; Khlidj, Yehya; Thakurathi, Priyesh; Hammad, Amer; Mohammed, Fathia; Almaadawy, Omar; Farhoud, Hassan; Ghaly, Ramy; Khan, Ubaid; et al. (Cardiovascular revascularization medicine, 2025)
Percutaneous micro-axial flow pumps (mAFP) are increasingly used for hemodynamic support during high-risk percutaneous coronary interventions (PCI) despite limited evidence supporting their effectiveness. We conducted a meta-analysis to assess the effectiveness and safety of mAFP use during non-emergent high-risk PCI procedures. Electronic databases were searched for studies comparing percutaneous mAFP versus control for non-emergent high-risk PCI. The primary outcome was the incidence of major adverse cardiac events (MACE). Eight studies (one randomized, seven observational) with 4688 patients were included. There were no significant differences in the risk of MACE within 30 days (RR 1.34; 95 % CI 0.73–2.47) or at 1 year (RR 1.08; 95 % CI 0.58–1.98) in patients treated with vs. without a mAFP during high-risk PCI. Nor was the risk of mortality different between groups. Peri-procedural complications, including acute kidney injury, major bleeding, blood transfusions, myocardial infarction, and stroke, were not increased with the mAFP. The subgroup of patients who received mAFP prior to PCI again had similar risk of MACE and mortality compared with the control. However, in this group, mAFP use was associated with higher in-hospital risks of major bleeding (RR 2.77; 95 % CI 1.28–5.98) and blood transfusion (RR 2.20; 95 % CI 1.17–4.15) and of in-hospital or 30-day myocardial infarction (RR 1.68; 95 % CI 1.03–2.73). mAFP use was not associated with improved outcomes among patients undergoing non-emergent high-risk PCI. Given the potential for selection bias, ongoing large-scale randomized trials are necessary to determine its impact on efficacy and safety. In 4688 patients undergoing non-emergent high-risk PCI, use of a percutaneous micro-axial flow pump did not reduce MACE or mortality at 30 days or 6 months, and pre-PCI use was linked to higher risks of bleeding and in-hospital MI, warranting further large-scale trials. [Display omitted] •This meta-analysis evaluated outcomes of micro-axial flow pumps in high-risk PCI.•No significant reduction in major adverse cardiac events was observed with mAFP use.•mAFP was associated with higher 90-day mortality but not at 30 days or 1 year.•In-hospital risks of acute kidney injury, stroke, or MI were not significantly different.•Pre-PCI use of mAFP increased risks of bleeding and transfusion in sensitivity analyses.